Speech-language disorder severity, academic success, and socioemotional functioning among multilingual and English children in the United States: The National Survey of Children’s Health - Foster, Matthew E.; Choo, Ai Leen; Smith, Sara A. (Frontiers in Psychology, 2023)
Research points to negative associations between educational success, socioemotional functioning, and the severity of symptoms in some speech-language disorders (SLDs). Nonetheless, the majority of studies examining SLDs in children have focused on monolinguals. More research is needed to determine whether the scant findings among multilinguals are robust. The present study used parent report data from the U.S. National Survey of Children’s Health (2018 to 2020) to gain a better understanding of the impacts of SLD severity on indicators of academic success and socioemotional functioning among multilingual (n=255) and English monolingual (n=5,952) children with SLDs. Tests of between-group differences indicated that multilingual children evidenced more severe SLDs, had lower school engagement, and had lower reports of flourishing than English monolingual children with SLDs. Further, a greater proportion of multilingual children with SLDs missed more school days than English monolinguals. However, multilinguals were less likely to bully others or have been bullied than monolinguals. While the previous between-group differences were statistically significant, they were small (vs ≤ 0.08). Increased SLD severity predicted an increased number of repeated school grades, increased absenteeism, and decreased school engagement, when age and socioeconomic status were controlled. Increased SLD severity also predicted greater difficulty making and keeping friends and decreased flourishing. The effect of SLD severity on being bullied was statistically significant for the monolinguals but not multilinguals. There was a statistically significant interaction for SLD severity and sex for school engagement and difficulty making and keeping friends for monolinguals but not multilinguals. The interactions indicated that school engagement decreased more for females than for males while difficulties making and keeping friends increased more for males than females as one’s SLD severity increased. While some findings were specific to monolinguals, tests of measurement invariance indicated that the same general pattern of relations among the variables were evident across the groups of multilinguals and monolinguals. These final findings can inform the interpretation of the results from both the current and future studies, while the overall findings can inform the development of intervention programs, thereby improving the long-term academic and socioemotional outcomes of children with SLDs.